2019
DOI: 10.57200/apjsbs.v16i0.165
|View full text |Cite
|
Sign up to set email alerts
|

Journal Writing In Solving Worded Problems: Does It Help?

Abstract: Concern about teaching problem solving and mathematical thinking has paved way for the development of a writing-to-learn approach in math. This study explored on college students’ experiences in solving worded math problems, and the use of journal writing as a strategy in solving problems. The students’ experiences as seen in their journal served as the baseline data in the study. In making the journals, the students focused on key words, relationships, processes and lessons learned through writing statements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Students suffer various difficulties and challenges, such as low motivation in learning Math (Fouze and Amit, 2017). Students can hardly solve worded math problems due to fear of problem-solving, poor comprehension, lack of knowledge of the problem presented, procedural errors, and difficulty level of the problem (Taban and Cadorna, 2019). Most students concluded that Mathematics is a complicated subject (Kislenko et al).…”
Section: Introductionmentioning
confidence: 99%
“…Students suffer various difficulties and challenges, such as low motivation in learning Math (Fouze and Amit, 2017). Students can hardly solve worded math problems due to fear of problem-solving, poor comprehension, lack of knowledge of the problem presented, procedural errors, and difficulty level of the problem (Taban and Cadorna, 2019). Most students concluded that Mathematics is a complicated subject (Kislenko et al).…”
Section: Introductionmentioning
confidence: 99%